Early recovery and employment outcome 13 years after first episode psychosis. (January 2019) - Strålin, Pontus; Skott, Maria; Cullberg, Johan
Highlights: Many cases of first episode psychosis have a potential for a good early recovery. Many cases of first episode psychosis have a potential for late stable employment. Many cases of first episode psychosis may end antipsychotics early after recovery. Abstract: 175 cases of first episode psychosis were recruited to the Parachute project in 1996–97. The program offered highly available and continuous psychosocial support and a cautious use of antipsychotic medication for 5 years from inclusion. Outcome-data for year 13 after inclusion, were retrieved from Swedish population registries on 161 of the original cases. During the first year after inclusion the cohort improved in the scores of the Brief Psychiatric Rating Scale (BPRS) and Global Assessment of Function (GAF) to median levels that later remained rather stable. By month 12 the median GAF score was 65. 68% of the cases were in remission from psychotic symptoms as assessed with BPRS. 38% of the cases in remission and 60% not in remission had prescriptions of antipsychotic medication by month 12. By year 13 after inclusion, 42% were in employment and 55% had any dispensation of antipsychotic medication. 70% of the cases with employment had no dispensations of antipsychotic medication. In conclusion, Many first episode psychosis cases that were offered extensive psychosocial support and cautious use of antipsychotic medication had good early recovery and good late employment outcome.